The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1530/eje-11-0755
|View full text |Cite
|
Sign up to set email alerts
|

MECHANISMS IN ENDOCRINOLOGY: Recent advances in cardiovascular aspects of polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) has been associated with increased cardiovascular risk (CVR) markers, but population studies have not clarified whether there is an increase in cardiovascular morbidity and mortality. Four different PCOS phenotypes resulted from the Rotterdam criteria that may differ in their CVR potential, thus introducing further complexity. This has led to studies using surrogate CVR markers including biomarkers in blood and imaging such as flow-mediated vasodilatation. In PCOS, both periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 75 publications
1
43
0
Order By: Relevance
“…Diabetes was often encountered in the study population of MtoF and FtoM in the study of Wierckx et al (27). 5) It is remarkable that women with hyperandrogenism have a high number of surrogate cardiovascular risk factors, but there is limited convincing evidence that high endogenous or exogenous androgens increase cardiovascular pathology (60). In FtoM, testosterone administration does not induce hyperinsulinism (54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes was often encountered in the study population of MtoF and FtoM in the study of Wierckx et al (27). 5) It is remarkable that women with hyperandrogenism have a high number of surrogate cardiovascular risk factors, but there is limited convincing evidence that high endogenous or exogenous androgens increase cardiovascular pathology (60). In FtoM, testosterone administration does not induce hyperinsulinism (54).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperandrogenic women with the polycystic ovarian syndrome have an established increased risk of developing type 2 diabetes (57) and many cardiovascular risks (58) but a still debated increased risk of cardiovascular disease (59). It is still not clear why, in view of the many cardiovascular risk factors, there is no overwhelming increase in cardiovascular morbidity and mortality in women with the polycystic ovarian syndrome (60). In a study comparing testosterone-treated FtoM with hyperandrogenic women with polycystic ovarian syndrome, we found that testosterone administration induced a decline in serum HDL and increase in triglycerides, but had no effect on insulin resistance, a frequent feature of PCOS (54).…”
Section: The Effects Of Testosterone Administration On Cardiovascularmentioning
confidence: 99%
“…On the other hand, androgen excess per se and related metabolic issues are typical areas of endocrinological interest, and the current survey by ESE clearly expresses the considerable interest of endocrinologists in Europe in the field. There are some differences between endocrinologists and gynecologists in the definition, diagnosis, and treatment of PCOS, as documented by a recent survey performed in Australia (9) and as shown by many review articles written by gynecologists or endocrinologists (11,12,13). Whereas the latter regarded androgen excess and menstrual irregularity as the major diagnostic criteria, the former were more likely to list ovarian morphology and menstrual irregularities as the main criteria, with androgenization further down the list.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in prepubertal or adolescents predisposed to the development of PCOS associated with obesity, early intervention to address dietary energy intake and exercise habits may prevent the development and onset of PCOS in these individuals. This in turn may prevent long-term cardiometabolic risk and adverse reproductive and fertility outcomes associated with PCOS (Alexander et al 2009, Sathyapalan & Atkin 2012.…”
Section: Hypothalamic Arc Neuropeptide and Peptide Expressionmentioning
confidence: 99%
“…The manifestation of PCOS in overweight-obese adolescents is likely to originate in prepuberty (Diamanti-Kandarakis et al 2007), predisposing individuals to increased cardiometabolic risk, including dyslipidemia and impaired glucose tolerance, leading to early development of type II diabetes and cardiovascular disease (Alexander et al 2009, Fulghesu et al 2010, Sathyapalan & Atkin 2012, Dantas et al 2013. Insulin resistance (IR) is strongly implicated in the etiology of PCOS (Baillargeon & Nestler 2006, Diamanti-Kandarakis & Dunaif 2012 and hyperinsulinemia has been shown to stimulate androgen production in ovarian thecal cells and to reduce hepatic sex-hormone binding globulin (SHBG) synthesis (Barbieri et al 1984, Nestler et al 1991.…”
Section: Introductionmentioning
confidence: 99%